High-throughput analysis of uridine insertion and deletion RNA editing in Perkinsela - David, Vojtěch (Jihočeská univerzita, 2015)
This thesis is a follow-up of my Bachelor thesis about the mitochondrial genome of kinetoplastid protist Perkinsela sp. This work introduces a novel approach in high-throughput analysis method of uridine insertion and deletion RNA editing, describes its background and proposes its further development. Its effect on the interpretation of U-indel editing, both in Perkinsela and in general, is demonstrated via attached manuscript which also introduces other biologically relevant aspects of Perkinsela mitochondrion.
High-throughput analysis of uridine insertion and deletion RNA editing in Perkinsela
Keywords: Perkinsela; RNA editing; kinetoplast; read mapping; transcriptome